2024
DOI: 10.3847/1538-4357/ad05c5
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Harmonics for the 1D Radiative Transfer Equation. II. Thermal Emission

Caoimhe M. Rooney,
Natasha E. Batalha,
Mark S. Marley

Abstract: Approximate methods for radiative transfer equations that are fast, reliable, and accurate are essential for the understanding of atmospheres of exoplanets and brown dwarfs. The simplest and most popular choice is the “two-stream method,” which is often used to produce simple yet effective models for radiative transfer in scattering and absorbing media. Toon et al. (hereafter, Toon89) outlined a two-stream method for computing reflected light and thermal spectra that was later implemented in the open-source ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Due to the generalized nature of the RT methods used here, our findings are likely applicable to atmospheres across the exoplanet spectrum, from ultrahot Jupiters to warm Neptunes and rocky planets. However, we caution conditions of high gravity and strong scattering on cloudy brown dwarfs, such as those tested in Rooney et al (2024), will need to be tested further before AAE and VIM can be recommended for brown dwarf modeling efforts. Software: DISORT and DISORT-twostr: http://www.rtatmocn.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Due to the generalized nature of the RT methods used here, our findings are likely applicable to atmospheres across the exoplanet spectrum, from ultrahot Jupiters to warm Neptunes and rocky planets. However, we caution conditions of high gravity and strong scattering on cloudy brown dwarfs, such as those tested in Rooney et al (2024), will need to be tested further before AAE and VIM can be recommended for brown dwarf modeling efforts. Software: DISORT and DISORT-twostr: http://www.rtatmocn.…”
Section: Discussionmentioning
confidence: 98%
“…In Rooney et al (2024), the Toon89 method was compared to a spherical harmonic (SH) method with the source function technique. They found that the Toon89 method produced spectral OLR differences of ∼20% or more at certain wavelengths compared to their DISORT reference calculations for their examples of cloudy brown dwarfs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations